1997
DOI: 10.1042/bj3230801
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of glucose-6-phosphate dehydrogenase in human cells sustaining oxidative stress

Abstract: Recent reports have demonstrated that glucose-6-phosphate dehydrogenase (G6PD) activity in mammalian cells is necessary in order to ensure cell survival when damage is produced by reactive oxygen intermediates. In this paper we demonstrate that oxidative stress, caused by agents acting at different steps in the biochemical pathway controlling the intracellular redox status, determines the increase in G6PD-specific activity in human cell lines of different tissue origins. The intracellular level of G6PD-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 40 publications
9
93
0
Order By: Relevance
“…Thus, the levels of G6PD have a dramatic effect on the susceptibility to apoptotic cell death induced by both agents. DISCUSSION We have already shown that G6PD expression is up-regulated by oxidants through a mechanism acting mainly on the rate of transcription of this gene (16). Here we show that this effect is specifically counteracted by NAC, an antioxidant that replenishes the GSH pool (35).…”
Section: G6pd-mediated Rise Of Gsh Levels 2754mentioning
confidence: 59%
See 2 more Smart Citations
“…Thus, the levels of G6PD have a dramatic effect on the susceptibility to apoptotic cell death induced by both agents. DISCUSSION We have already shown that G6PD expression is up-regulated by oxidants through a mechanism acting mainly on the rate of transcription of this gene (16). Here we show that this effect is specifically counteracted by NAC, an antioxidant that replenishes the GSH pool (35).…”
Section: G6pd-mediated Rise Of Gsh Levels 2754mentioning
confidence: 59%
“…Effect Is Specifically Counteracted by NAC-We have already reported that several oxidative drugs, whose final effect is to decrease the intracellular GSH pool, enhanced the expression of G6PD and that this regulation is achieved at the levels of transcription of this gene (16). In the first experiment, human Hep3B cells were treated with diamide, a powerful sulfhydryl group-oxidizing agent that specifically causes the depletion of glutathione without any other observable effect (33).…”
Section: G6pd Expression Is Enhanced By Gsh-depleting Drugs: Thismentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced GSH levels and resistance to oxidation were demonstrated in different cells after an oxidant insult mediated by an increased G6PD expression [30,31]. An efficient level of GSH is crucial for the maintenance of an adequate metabolism, antioxidant protection of Hb, and the membrane integrity of the RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…As a new result, a reduced GSH recycling capacity of the RBCs was demonstrated in the hypertensive pregnant patients, which could be a harmful factor, predisposing them to oxidative hemolysis. We suggest that a misadaptation to the normal pregnancy-induced oxidative stress in hypertensive patients may be a consequence of either a redox-sensitive inactivation of G6PD, mediated by oxidants from activated neutrophils [34], or an insufficient induction of the enzyme G6PD [31]. Fig.…”
Section: Discussionmentioning
confidence: 99%